REFLECTION OF ENGLISH READING CURRICULUM IN JUNIOR HIGH SCHOOL TEXTBOOKS: IMPLICATION FOR CURRICULUM DEVELOPMENT - Bukhori Bukhori (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
This study investigates the reflection of English reading curriculum in Junior High School textbooks in terms of types of syllabus, reading tasks and cognitive level of reading tasks. Two books have been employed as documents to be analyzed in this research. The first book is Bahasa Inggris Sekolah Pertama Kelas VIII Edisi 4 which is one of electronic textbooks (Buku Sekolah Elektronik (BSE)) published by Department of National Education. The second book is English on Sky (EOS)2 for Junior High School Students Year VIII from Erlangga publisher. The findings suggested that both BSE and EOS have reflected a part of English reading curriculum. In this case BSE is better than EOS. However, both textbooks need to be improved in fulfilling the curriculum demand in terms of types of reading tasks and cognitive levels of reading tasks. Based on the research findings, some recommendations for curriculum development are finally presented.